Analisis Pengendalian Persediaan Bahan Baku Menggunakan Metode Material Requirement Planning (MRP) Pada Risma Brownies & Cake Gemolong - Karunia Fadillatul Firdaus; Erni Widajanti (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
Risma Brownies & Cake Gemolong is a business operating in the food industry. The problem that the company is hoping for is whether control of raw material inventory at Risma Brownies & Cake Gemolong is efficient and whether the MRP method can make control of raw material inventory at Risma Brownies & Cake Gemolong efficient. The aim of this research is to analyze the efficiency of raw material inventory control at Risma Brownies & Cake Gemolong and to analyze the application of the MRP method to make raw material inventory control efficient at Risma Brownies & Cake Gemolong. The method used in this research is the Material Requirement Planning (MRP) method, with data analysis techniques using Lot For Lot (LFL), Economic Order Quantity (EOQ), and Period Order Quantity (POQ) techniques. The data required is a general description of Risma Brownies & Cake, organizational structure, production process, raw material usage data, raw material inventory data, holding cost data, and ordering cost data. Data collection techniques using interviews. Based on the results of the research that has been carried out, the researcher concluded that the most efficient method applied at Risma Brownies & Cake is the Period Order Quantity (POQ) method. The LFL method produces inventory costs of IDR 468,000, the EOQ method produces inventory costs of IDR 3,663,000, while the POQ method can produce inventory costs of IDR 468,000